Designing information about medicines for people - van der Waarde, Karen (InfoDesign, 2008)
In Europe, it is obligatory to provide written information with every medicine, usually in the format of a package leaflet. These leaflets are fairly long and are densely printed on very thin paper. Readability testing and contextual inquiries indicate the practical problems of current package leaflets: they do not reach appropriate minimal performance levels. This is likely to be caused by the internal conflicts in the legislation and guidance, and the poor co-operation of involved stakeholders. The experience with the ‘writing-designing-testing process’ in combination with a critical look at the current guidelines provides clear pointers for further developments. It is necessary to develop alternatives that start from the perspective of patients, are performance driven, and are context related. Within the current legal framework, it is unlikely that it is possible to develop package leaflets that ‘enable people to use medicines appropriately’. Alternative designs will be seen as ‘illegal’ and will not be allowed to be used in practice. However, these alternatives are vital to stimulate discussions between stakeholders about legislation, guidelines, and appropriate information about medicines for patients.